Fundamental solution of the Cauchy problem for the Shilov-type parabolic systems with coefficients of bounded smoothness - Litovchenko, V. A.; Unguryan, G.M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
Under the condition of minimal smoothness of the coefficients, we construct the fundamental solution of the Cauchy problem and study the principal properties of this solution for a special class of linear parabolic systems with bounded variable coefficients covering the class of Shilov-type parabolic systems of nonnegative kind.